Non-linear associations between blood pressure and clinical outcomes in atrial fibrillation: A systematic review and dose-response meta-analysis - Elnaz Shahmohamadi; Alessandra Pina; Adrian D Elliott; Jonathan P Ariyaratnam; Melissa E Middeldorp; Prashanthan Sanders (Europace, 2026)
Abstract Background and Aims Hypertension carries the highest attributable risk for atrial fibrillation (AF) and strongly influences clinical outcomes such as stroke and death; however, the optimal blood pressure targets in individuals with AF remain poorly defined. We aimed to characterise the dose-response relationship between systolic blood pressure (SBP) and diastolic blood pressure (DBP) and ischaemic stroke, all-cause mortality, and intracranial haemorrhage. Methods We systematically searched MEDLINE, Embase, and Scopus for studies reporting outcomes in AF stratified by SBP and DBP. A two-stage dose-response meta-analysis used restricted cubic splines to model non-linearity, with within-study correlation handled by the Greenland–Longnecker method. Results Twenty-three studies (17 cohorts; n = 476,750) were included. SBP demonstrated a U-shaped association with all-cause mortality, with the lowest risk at 134 mmHg (RR 0.92, 0.86–0.98 versus 120 mmHg). DBP exhibited a J-shaped association, with the lowest risk at 83 mmHg (RR 0.99, 0.97–1.02). In contrast to mortality, the risks of ischaemic stroke, intracranial haemorrhage, and stroke or systemic embolism rose progressively with SBP, with a steepening gradient. At 140 versus 120 mmHg, the RR was 1.51 for intracranial haemorrhage against 1.08 for ischaemic stroke, reaching 1.99 versus 1.14 at 150 mmHg. Conclusion Systolic blood pressure exhibits a U-shaped relationship with all-cause mortality in patients with AF, balancing against a monotonic increase in ischemic stroke and intracranial haemorrhage at higher pressures. A pragmatic target SBP of 120–130 mmHg with DBP kept above approximately 75–80 mmHg, appears to optimize the balance between stroke prevention, bleeding risk, and survival.